Resting State Functional Connectivity Signatures of MRgFUS Vim Thalamotomy in Parkinson's Disease: A Preliminary Study - Stanziano, Mario; Golfrè Andreasi, Nico; Messina, Giuseppe; Rinaldo, Sara; Palermo, Sara; Verri, Mattia; Demichelis, Greta; Medina, Jean Paul; Ghielmetti, Francesco; Bonvegna, Salvatore; Nigri, Anna; Frazzetta, Giulia; et al. (Frontiers in Neurology, 2022)
Magnetic Resonance-guided high-intensity Focused Ultrasound (MRgFUS) of the thalamic ventral intermediate nucleus (Vim) for tremor has increasingly gained interest as a new non-invasive alternative to standard neurosurgery. Resting state functional connectivity (rs-FC) correlates of MRgFUS have not been extensively investigated yet. A ROI-to-ROI rs-FC MRI “connectomic” analysis focusing on brain regions relevant for tremor was conducted on fifteen tremor-dominant Parkinson’s disease patients who underwent MRgFUS. We tested whether rs-FC between tremor-related areas was modulated by MRgFUS at 1- and 3-months post-operatively and whether such changes correlated with individual clinical outcomes assessed by the MDS-UPDRS-III sub items for tremor. Significant increase in FC was detected within bilateral primary motor (M1) cortices, as well as between bilateral M1 and crossed primary somatosensory cortices, and between pallidum and the dentate nucleus of the untreated hemisphere. Correlation between disease duration and FC increase at 3-months was found between the putamen of both cerebral hemispheres and the Lobe VI of both cerebellar hemispheres, as well as between the Lobe VI of untreated cerebellar hemisphere with bilateral supplementary motor area (SMA). Drop-points value of MDS-UPDRS at 3-months correlated with post-treatment decrease in FC between the anterior cingulate cortex and bilateral SMA, as well as between the Lobe VI of treated cerebellar hemisphere and interpositus nucleus of untreated cerebellum. Tremor improvement at 3-months expressed as percentage of intra-subject MDS-UPDRS changes correlated with FC decrease between bilateral occipital fusiform gyrus and crossed Lobe VI and Vermis VI. Good responders (≥50% of baseline tremor improvement) showed reduced FC between bilateral SMA, between the interpositus nucleus of untreated cerebellum and the Lobe VI of treated cerebellum, as well as between the untreated SMA and the contralateral putamen. Good responders were characterized at baseline by crossed hypoconnectivity between bilateral putamen and M1, as well as between the putamen of the treated hemisphere and the contralateral SMA. We conclude that MRgFUS can effectively modulate brain FC within the tremor network. Such changes are associated with clinical outcome. The shifting mode of integration among the constituents of this network is therefore susceptible to external redirection despite the chronic nature of PD.